Children and adolescents’ positive youth development qualities and internet addiction during the COVID-19 pandemic: A longitudinal study in China - Wang, Zhuo; Hong, Binxue; Zhang, Yanyan; Su, Ya; Li, Minghui; Zhao, Li; Jia, Peng (Frontiers in Psychiatry, 2023)
Backgrounds: Recent studies have shown that the qualities of positive youth development (PYD) enable children and adolescents to cope with developmental challenges. During the COVID-19 pandemic, there is still a lack of reporting on changes in children and adolescents' PYD qualities and Internet addiction and their relationship. This study investigated the association between PYD qualities and Internet addiction among the children and adolescents who have experienced the COVID-19 lockdown. Methods: A school-based cohort survey was launched in December 2019 (Wave 1, before COVID-19 lockdown) and followed up in June 2020 (Wave 2, after COVID-19 lockdown). The Chinese PYD scale (80 items, scoring 80-480) and Young's Internet addiction test (20 items, scoring 20-100) were used to evaluate the children and adolescents' PYD qualities and the degree of their Internet addiction, respectively. Cross-sectional regressions, longitudinal regressions and cross-lagged panel model were used to examine the association between PYD qualities and Internet addiction. Results: 7,985 children and adolescents completed both waves of surveys. Compared with children and adolescents before lockdown (Wave 1), their total PYD quality dropped from 4.99 to 4.96 after COVID-19 lockdown (Wave 2), and the mean score for Internet addiction rose from 35.56 to 36.16. Cross-sectional analysis showed that the total PYD quality of children and adolescents in two waves was negatively correlated with the degree of Internet addiction during the same period, with β of -6.10 and -6.95, respectively. Longitudinal analysis showed that children and adolescents' total PYD quality in Wave 1 was negatively correlated with the Wave 2 of Internet addiction and the change between the two waves of Internet addiction, with β of -3.35 and -0.26, respectively. Cross-lagged panel models showed a negative bilateral relationship between total PYD quality and Internet addiction. Conclusions: During the COVID-19 pandemic, the qualities of children and adolescents' PYD declined, which makes children and adolescents more vulnerable to Internet addiction. Therefore, it is necessary to widely implement programs in China that can comprehensively improve the qualities of children and adolescents' positive development to prevent Internet addiction, especially after the blockade due to public health emergencies.